2020
DOI: 10.1039/d0ta00143k
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in morphology optimization in perovskite solar cell

Abstract: Hybrid organic–inorganic halide perovskite based solar cell technology has passed through a phase of unprecedented growth in the efficiency scale from 3.8% to above 25% within a decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(136 citation statements)
references
References 165 publications
2
134
0
Order By: Relevance
“…The increasing rate formula is Rate = ( (J m −J n )/(m−n) J n ) × 100%, where J m and J n are the dark current densities on day m and day n. The calculated rate of change in dark current density is about 0.255% per day. The good morphology and crystallinity of epitaxial films benefit better stability than polycrystalline films (Salim et al, 2015;Tailor et al, 2020). The comparison of photoelectric performance between different MAPbI 3 -based devices is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing rate formula is Rate = ( (J m −J n )/(m−n) J n ) × 100%, where J m and J n are the dark current densities on day m and day n. The calculated rate of change in dark current density is about 0.255% per day. The good morphology and crystallinity of epitaxial films benefit better stability than polycrystalline films (Salim et al, 2015;Tailor et al, 2020). The comparison of photoelectric performance between different MAPbI 3 -based devices is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of the perovskite layer can be controlled through a number of processes, such precursor solution processing and aging [62], perovskite film annealing [63], and incorporation of additives in the perovskite material [64]. It has also been demonstrated that optimizing the crystallinity of the perovskite absorption layer is crucial to the development of perovskite solar cells with high power conversion efficiencies [65], as improved crystallinity leads to enhanced film uniformity, thus increasing device efficiency [66].…”
Section: Future Outlook and Challengesmentioning
confidence: 99%
“…Among numerous organic–inorganic hybrid perovskites, (CsPbI 3 ) 0.05 [(FAPbI 3 ) 0.85 (MAPbBr 3 ) 0.17 ] 0.95 is the most promising material due to its superior photovoltaic performance and the stability. [ 7–10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Among numerous organic-inorganic hybrid perovskites, (CsPbI 3 ) 0.05 [(FAPbI 3 ) 0.85 (MAPbBr 3 ) 0.17 ] 0.95 is the most promising material due to its superior photovoltaic performance and the stability. [7][8][9][10] Although various deposition methodologies have been used to fabricate the perovskite films, the one-step spin-coating deposition assisted by an antisolvent is still regarded as an efficient and widely accepted approach. [11,12] Nevertheless, the reproducibility of high-quality perovskite films highly depends on the skilled and experienced operator.…”
Section: Introductionmentioning
confidence: 99%